"Play with me": Student perspectives on collaborative chamber music instruction. (April 2022) - Zhukov, Katie; Sætre, Jon Helge
This article reports on a pilot project conducted in Australia and Norway evaluating new approaches to collaborative chamber music instruction in higher education settings. Following suggestions from the literature on collaborative and group learning in music, chamber music tuition was chosen as a suitable context to examine the possibility of teaching-through-playing and the impact of such an approach on students' collaborative learning and their induction into the professional music community. Two groups of staff and students in each institution volunteered to participate in the project and implemented their own rehearsal schedule. Student focus group interviews were conducted after the final performance of rehearsed repertoire, and transcripts were analyzed by two researchers independently for the emerging themes and refined through iterative discussions. Key findings include students being inspired by working with experienced staff in a professional setting, learning the skills of ensemble playing such as effective rehearsal techniques, understanding of stylistic conventions, specific technical, musical and co-ordination skills, greater experimentation, positive impact of group discussions, and a more collaborative atmosphere. Students found it challenging to alter power roles, as the ingrained attitudes of teacher-led approaches prevailed. This project has shown that teaching-through-playing chamber music is a viable approach for developing students' musical and social skills by providing them with authentic professional experiences. We propose an alternative model of higher education performance teaching that is more collaborative and participatory.